Therapeutic implications of C. albicans-S. aureus mixed biofilm in a murine subcutaneous catheter model of polymicrobial infection. Issue 1 (31st December 2021) - Vila, Taissa; Kong, Eric F.; Montelongo-Jauregui, Daniel; Van Dijck, Patrick; Shetty, Amol C.; McCracken, Carrie; Bruno, Vincent M.; Jabra-Rizk, Mary Ann
ABSTRACT: Biofilm-associated polymicrobial infections tend to be challenging to treat. Candida albicans and Staphylococcus aureus are leading pathogens due to their ability to form biofilms on medical devices. However, the therapeutic implications of their interactions in a host is largely unexplored. In this study, we used a mouse subcutaneous catheter model for in vivo -grown polymicrobial biofilms to validate our in vitro findings on C. albicans -mediated enhanced S. aureus tolerance to vancomycin in vivo . Comparative assessment of S. aureus recovery from catheters with single- or mixed-species infection demonstrated failure of vancomycin against S. aureus in mice with co-infected catheters. To provide some mechanistic insights, RNA-seq analysis was performed on catheter biofilms to delineate transcriptional modulations during polymicrobial infections. C. albicans induced the activation of the S. aureus biofilm formation network via down-regulation of the lrg operon, repressor of autolysis, and up-regulation of the ica operon and production of polysaccharide intercellular adhesin (PIA), indicating an increase in eDNA production, and extracellular polysaccharide matrix, respectively. Interestingly, virulence factors important for disseminated infections, and superantigen-like proteins were down-regulated during mixed-species infection, whereas capsular polysaccharide genes were up-regulated, signifying a strategy favoring survival, persistence and host immune evasion. In vitro follow-up experiments using DNA enzymatic digestion, lrg operon mutant strains, and confocal scanning microscopy confirmed the role of C. albicans -mediated enhanced eDNA production in mixed-biofilms on S. aureus tolerance to vancomycin. Combined, these findings provide mechanistic insights into the therapeutic implications of interspecies interactions, underscoring the need for novel strategies to overcome limitations of current therapies.